Pemanfaatan K-Means Untuk Meningkatkan Penjualan (Studi Kasus: Alya Collection) - Safitri, Windi Aulia; Saputra, Herman; Syafnur, Afdhal (STMIK Royal Kisaran, 2025)
Abstract: In a competitive digital era, business owners such as Alya Collection face challenges in determining the right fashion products to offer to consumers. Relying on intuition without data support often results in inaccurate and potentially detrimental decisions. This study aims to assist the sales decision-making process by applying a data mining method using the K-Means Clustering algorithm. This method was used to group sales data from February 2024 to January 2025 into three categories: best-selling, least-selling, and non-selling products. The study was conducted using a quantitative approach, through sales data collection and direct interviews with store owners. The system was built using the PHP programming language and MySQL database, and designed with tools such as UML, DFD, and ERD. The results of this clustering system are expected to provide strategic information useful for Alya Collection in planning stock, promotions, and product development, thereby increasing sales effectively and efficiently. Keywords: data mining; k-means; sales; alya collection; information system Abstrak: Dalam era digital yang kompetitif, pemilik usaha seperti Alya Collection menghadapi tantangan dalam menentukan produk fashion yang tepat untuk ditawarkan kepada konsumen. Ketergantungan pada intuisi tanpa dukungan data seringkali mengakibatkan keputusan yang kurang akurat dan berisiko merugikan. Penelitian ini bertujuan untuk membantu proses pengambilan keputusan penjualan dengan menerapkan metode data mining menggunakan algoritma K-Means Clustering. Metode ini digunakan untuk mengelompokkan data penjualan dari Februari 2024 hingga Januari 2025 ke dalam tiga kategori: produk terlaris, kurang laris, dan tidak laris. Penelitian dilakukan dengan pendekatan kuantitatif, melalui pengumpulan data penjualan serta wawancara langsung dengan pemilik toko. Sistem yang dibangun menggunakan bahasa pemrograman PHP dan database MySQL, serta dirancang dengan alat bantu seperti UML, DFD, dan ERD. Hasil dari sistem klasterisasi ini diharapkan dapat memberikan informasi strategis yang berguna bagi Alya Collection dalam merencanakan stok, promosi, serta pengembangan produk, sehingga mampu meningkatkan penjualan secara efektif dan efisien. Kata kunci: data mining; k-means clustering; penjualan; alya collection; sistem informasi